A case report on localised laryngeal amyloidosis - Agius, Marija; Grima, Tara; Cvorovic, Maja; Babic, Darko; Borg, Charles (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Amyloidosis is a rare disease which involves deposition of amyloid in the tissues. Very rarely, amyloid can be deposited in a single organ giving rise to localised amyloidosis. In the present study, a rare case of localised amyloid deposition in the larynx in a young patient was presented. It is a slow progressive disease and often diagnosed late and is confirmed by biopsy results.